Vegetative propagation of conifers for enhancing landscaping and tree breeding. Proceedings of the Nordic meeting held in September 10th-11th 2008 at Punkaharju, Finland. - (:unkn) unknown (Finnish Forest Research Institute, 2009)
The Nordic meeting Vegetative propagation of conifers for enhancing landscaping and tree breeding was held at Punkaharju, Finland, in September 10-11th , 2008. The aim of the meeting was to share ideas and experiences among researchers, tree breeders, and commercial plant producers /nurseries, together with customers acting in landscaping or in forestry on the potentials and challenges in vegetative propagation of the Nordic conifers. There were altogether 54 registrated participants representing different stakeholders from six European countries.The meeting was hosted by Metla - Finnish Forest Research Institute, Punkaharju Research Unit, and kindly supported by GENECAR, Nordic Centre of Advanced Research in Forest Genetics and Tree Breeding, and The Foundation for Forest Tree Breeding in Finland. The information presented by the speakers during the meeting sessions, as well as by some of the posters is collected into this proceedings publication in the form of extended abstracts. The topics discussed are the following: I) Tree breeding framework, II) Landscaping framework, III) Technical issues grafting and rooting of cuttings, and IV) Technical issues potentials of tissue culture, and V) Collaboration and future sights containing also information on funding possibilities. In addition, the outcome of the group discussions focusing on the topics How to facilitate the use of conifers as ornamentals? and Development of vegetative propagation techniques is shortly reviewed.
Myös luvuittain 18 tiedostona
Keywords: havupuut; juuripistokas; kasvullinen lisäys; kloonitestaus; koristepuut; puunjalostus; solukkoviljely; varttaminen; clonal testing; conifers; grafting; ornamental; rooted cuttings; tissue culture; tree breeding; vegetative propagation